2015
DOI: 10.1097/iop.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Features of Nasal Mucosa Treated with Topical and Circumostial Injection of Mitomycin C

Abstract: Both topical and COS-MMC show profound changes in nasal mucosa with more marked changes in COS-MMC group. These changes being limited in nature may help in enhancing the success of dacryocystorhinostomy by preventing cicatricial changes of the ostium, especially in high-risk cases such as revision and post-traumatic dacryocystorhinostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Under TEM, the cells were highly swollen with cytoplasm after the H 2 O 2 treatment, which may cause the synthesis of glycoproteins, steroid hormones and lipids, resulting in functional damage (Ali, Baig, Lakshman, & Naik, 2015). In the case of dead cells, the nuclear membrane was incomplete, the mitochondrial membrane in the cytoplasm was incomplete, and the ridge was blurred (Hochstrasser & Sedat, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Under TEM, the cells were highly swollen with cytoplasm after the H 2 O 2 treatment, which may cause the synthesis of glycoproteins, steroid hormones and lipids, resulting in functional damage (Ali, Baig, Lakshman, & Naik, 2015). In the case of dead cells, the nuclear membrane was incomplete, the mitochondrial membrane in the cytoplasm was incomplete, and the ridge was blurred (Hochstrasser & Sedat, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The nasal fibroblasts showed a dramatic structural response to MMC: Intracellular edema, pleomorphic and vesicular mitochondria, dilated smooth and rough endoplasmic reticulum, and chromatin condensation. [ 12 ]…”
Section: The Evidence: Does Mitomycin-c Really Help?mentioning
confidence: 99%
“…It has been used widely in other ophthalmic procedures like glaucoma filtration surgery and pterygium excision to enhance surgical success. Concerning its application in DCR, Ali et al demonstrated that both topical and circumostial injection of MMC induced ultrastructural changes within the fibroblasts, in particular, intracellular edema, pleomorphic, and vesicular mitochondria, dilated smooth and rough endoplasmic reticulum, and chromatin condensation [18]. Laboratory test on primary cultures of human nasal mucosal fibroblasts showed that application of MMC 0.4 mg/ ml beyond 5 min and 0.5 mg/ml beyond 3 min caused extensive cell death when compared with controls.…”
Section: Discussionmentioning
confidence: 98%